Estampes et revolution, 200 ans après. - Nardin, Anne (Paris : Centre National des Arts Plastiques, 1989)
Adami, Valerio ; Alberola, Jean-Michel ; Appel, Karel ; Arroyo, Eduardo ; Baselitz, Georg ; Ben ; Blais, Jean-Charles ; Bouillon, François ; Breytenbach, Breyten ; Brus, Günter ; Buraglio, Pierre ; Burgin, Victor ; Camara, Fodé ; Chambas, Jean-Paul ; Cucchi, Enzo ; Dezeuze, Daniel ; Dietman, Erik ; Dimitrijevic, Braco ; Errò ; Favier, Philippe ; Furudoi, Koji ; Gac, Jean Le ; Gäfgen, Wolfgang ; Goldstein, Zvi ; Golub, Leon ; Gonzalez de Armas, Jesus ; Immendorff, Jörg ; Isou, Isidore ; Kabakov, Ilya ; Kermarrec, Joël ; Klasen, Peter ; Kolar, Jiri ; Kruger, Barbara ; Leonilson ; Lüpertz, Markus ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Monory, Jacques ; O'Olivier, Olivier ; Oldenburg, Claes ; Parré, Michel ; Paschke, Ed ; Poli, Jacques ; Polke, Sigmar ; Pommereulle, Daniel ; Rainer, Arnulf ; Rancillac, Bernard ; Raysse, Martial ; Recalcati, Antonio ; Rinke, Klaus ; Sanejouand, Jean-Michel ; Sarkis ; Saul, Peter ; Saura, Antonio ; Segui, Antonio ; Serra, Richard ; Spoerri, Daniel ; Takis ; Tàpies, Antoni ; Telemaque, Hervé ; Titus-Carmel, Gérard ; Zeimert, Christian
Frans
Estampes et revolution, 200 ans après, Centre National des Arts Plastiques, Paris, 27.06.1989 - 27.08.1989
boek